Electromagnetic nondestructive evaluation (XIX) - Yusa, Noritaka; Uchimoto, Tetsuya; Kikuchi, Hiroaki (Studies in applied electromagnetics and mechanics ;, 2016)
ENDE workshops aim to provide an international forum for discussion on the state-of-the-art and perspectives in the field of electromagnetic nondestructive methods from the point of view of science and technology, as well as their applications in industry and engineering, which have contributed to the development of nondestructive testing and evaluation techniques using electromagnetic fields.